Permanently online—always stressed out? The effects of permanent connectedness on stress experiences - Freytag, Anna; Knop-Huelss, Katharina; Meier, Adrian; Reinecke, Leonard; Hefner, Dorothée; Klimmt, Christoph; Vorderer, Peter (Human Communication Research, 2021)
Concerns have been expressed that permanent online connectedness might negatively affect media user’s stress levels. Most research has focused on negative effects of specific media usage patterns, such as media multitasking or communication load. In contrast, users’ cognitive orientation toward online content and communication has rarely been investigated. Against this backdrop, we examined whether this cognitive orientation (i.e., online vigilance with its three dimensions salience, reactibility, monitoring) is related to perceived stress at different timescales (person, day, and situation level), while accounting for the effects of multitasking and communication load. Results across three studies showed that, in addition to multitasking (but not communication load), especially the cognitive salience of online communication is positively related to stress. Our findings are discussed regarding mental health implications and the origins of stress.<br